Empowered or Overlooked? Examining the Role of Employment Status in Public Welfare Workers’ Self-Efficacy and Job Satisfaction - Aquino, Gene Kathlyn (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2025)
Employee well-being is crucial to organizational success, particularly in public service sectors where job satisfaction and self-efficacy directly impact performance. This study explores the relationship between self-efficacy, job satisfaction, and employment status among personnel from a public social welfare agency. A total of 215 employees, including 31 permanent, 53 contractual, and 131 contract of service workers, were randomly selected for participation. Data were collected using the New General Self-Efficacy Scale (NGSE) and the Minnesota Satisfaction Questionnaire (MSQ). Findings revealed consistently high levels of self-efficacy and job satisfaction across employment types, with no significant statistical differences between groups. A positive correlation was identified between self-efficacy and job satisfaction, indicating that employees with greater belief in their capabilities experience higher job fulfillment. However, this relationship was weaker among contractual employees, likely due to job insecurity. Moreover, the study highlights the vital role of social services and camaraderie in boosting self-efficacy and satisfaction, particularly during times of crisis. These findings imply that the nature of public social workers' jobs, which include assisting disadvantaged populations and delivering necessary services, naturally raises their levels of self-efficacy and job satisfaction across all job categories.